Probiotic candidates of lactic acid bacteria from fermented food cincalok and tempoyak from Kalimantan, Indonesia - RETNO MURWANI; REFA ANGGRAENI; AMBARIYANTO AMBARIYANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Murwani R, Anggraeni R, Ambariyanto A. 2024. Probiotic candidates of lactic acid bacteria from fermented food cincalok and tempoyak from Kalimantan, Indonesia. Biodiversitas 25: 2705-2712. Lactic acid bacteria (LAB) belong to beneficial bacteria with the potential as probiotics to prevent pathogenic bacterial infections, improving digestive enzyme activity and the immune system. The objective of this research was to determine the probiotic potential of five lactic acid bacterial species isolated from fermented foods and to evaluate their antibacterial activity against pathogenic Bacillus subtilis, Bacillus cereus, Escherichia coli, Klebsiella pneumoniae, and Staphylococcus nepalensis. The gastric simulation test results showed a significant decrease in all five LAB isolates from 109 to 108 CFU/mL (P<0.05). Subsequent intestinal simulation decreased the number of Levilactobacillus brevis and Lactiplantibacillus plantarum numbers from 108 to 107 CFU/mL (P<0.05), which remains high. All five bacterial strains were found negative for the DNase test. In the hemolytic test, only Enterococcus faecalis and Pisciglobus halotolerans lysed red blood cells but not Tetragenococcus halophilus, L. brevis, and L. plantarum. In conclusion, T. halophilus, L. brevis, and L. plantarum were promising probiotic candidates. Further in vivo studies are necessary to test the probiotic effect of these three LAB strains.